Upaya meningkatkan kompetensi guru dalam menyusun RPP melalui supervisi akademik dengan teknik pertemuan individual di sekolah dasar - Widowati Widowati (Universitas Sebelas Maret, 2022)
Learning planning is a very important step before the implementation of learning.Careful planning is needed so that the implementation of learning runs effectively. Learningplanning is poured into the Learning Implementation Plan (RPP) or several other terms such aslearning design, learning scenarios. RPP contains KD, indicators to be achieved, material to bestudied, learning methods, learning steps, learning media, and learning resources andassessments. In this school action research consists of two cycles, namely cycle I and cycle 2.Where in each cycle consists of action planning, action implementation, observation andreflection. This research was conducted on teachers of SD Negeri Gondowangi 1 in semester 2of the 2015/2016 academic year. Data collection in cycles I and II used interviews andquestionnaires. The analysis technique was carried out qualitatively and quantitatively.This study aims to improve the competence of teachers through the making of LearningImplementation Plans. The results showed that with the supervision of the principal there wasan increase. The teacher's assessment results on average reached a percentage value of 79.54 to91.13, an increase of 11.59 after academic supervision was carried out with individual meetingtechniques. Therefore, it is expected to always improve their performance in learning so thatthe quality of education at SDN Gondowangi will increase.